2008
DOI: 10.1115/1.2900719
|View full text |Cite
|
Sign up to set email alerts
|

Biological Modeling and Evolution Based Synthesis of Metamorphic Mechanisms

Abstract: A methodology for synthesis and configuration design of metamorphic mechanisms is developed in this paper based on biological modeling and genetic evolution with biological building blocks. The goal is to conceive an appropriate source-metamorphic-mechanism configuration when the multiple phases of kinematic functions are given. The key enabler is the way of developing genetic evolution in modeling and design by capturing the metamorphic configuration characteristics. With the unique characteristic of achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The study concluded that mechanisms can change their topology through change of kinematic joints and special mechanism configurations. Mechanism and Machine Theory 45 (2010) [1864][1865][1866][1867][1868][1869][1870][1871][1872][1873][1874][1875][1876] Recently, Zhang and Dai [21] developed a methodology for synthesis and configuration design of metamorphic mechanisms based on biological modelling and genetic evolution. Basic combination of links and joints was taken as metamorphic cells and genes to form the source-metamorphic mechanism that evolves into various topology configurations for expected working configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that mechanisms can change their topology through change of kinematic joints and special mechanism configurations. Mechanism and Machine Theory 45 (2010) [1864][1865][1866][1867][1868][1869][1870][1871][1872][1873][1874][1875][1876] Recently, Zhang and Dai [21] developed a methodology for synthesis and configuration design of metamorphic mechanisms based on biological modelling and genetic evolution. Basic combination of links and joints was taken as metamorphic cells and genes to form the source-metamorphic mechanism that evolves into various topology configurations for expected working configurations.…”
Section: Introductionmentioning
confidence: 99%
“…A method for constructing original metamorphic mechanisms from biological modeling and genetic evolution was introduced in Wang and Dai (2007) and Zhang et al (2008). In this paper, based on Eq.…”
Section: Constructing the Original Metamorphic Mechanismmentioning
confidence: 99%
“…Recognizing that the concept of metamorphic mechanisms was based on the biological evolution principle, Zhang et al [18,19] proposed the metamorphic elements and metamorphic evolutionary techniques for the first time.…”
Section: Originality Of Origami Mechanismsmentioning
confidence: 99%